TWO WRONGS - Reid, Rebecca (Journalist) (London : Corgi, an imprint of Transworld, 2021)
"When Chloe goes to university and meets wild, carefree Zadie, she is utterly seduced by her and her lifestyle. It doesn't take long for Chloe to ditch her studies in favour of all-night parties at Zadie's huge house off campus. But when something goes badly wrong one night and Zadie disappears in the aftermath, Chloe knows she should have done more to help her friend. It's something she'll always regret. Fifteen years later, Chloe finally gets the chance to make it right. But in order to do so, she'll have to put everything at stake. How far would you go to correct the mistakes of your past?
Keywords: Female friendship -- Fiction; Missing persons -- Fiction; Disappeared persons -- Fiction; Justice -- Fiction; Self-sacrifice -- Fiction; Psychological fiction; Thrillers (Fiction)